Aluminum lactate role in improving hydration and drying behavior of MgO-bonded refractory castables. Issue 10 (July 2020) - Fini, D.S.; Miguel, V.C.; Pinto, V.S.; Pandolfelli, V.C.; Moreira, M.H.; Luz, A.P.
Abstract: Developing MgO-bonded castables is still an important subject for refractory producers and end-users based on the expansive character of the in-situ Mg(OH)2 formation. Considering that magnesia undergoes hydration when exposed to water and the generated hydrated phase needs to be properly accommodated in the resulting microstructure to inhibit the generation of cracks, it is very important to find out alternatives to control/change the MgO hydration reaction rate, which may help to optimize the permeability and green mechanical strength of the castables. Therefore, fast and safer drying of such refractories can be carried out when adjusting Mg(OH)2 generation with proper additives. This research investigated the use of aluminum lactate (AL) as a likely additive to change the hydration and drying behavior of vibratable castables bonded with different MgO sources (dead burnt, caustic or fumed one). Firstly, XRD, TG and DSC measurements of magnesia-based aqueous suspensions were evaluated to identify the AL effect on changing the hydration reaction products during the curing and drying steps. After that, Al2 O3 –MgO refractories were prepared and their flowability, curing behavior, cold flexural strength, apparent porosity, permeability and explosion resistance were evaluated. The results indicated that, instead of Mg(OH)2, Mg6 Al2 (OH)16 (OH)2 .4.5H2 O/Mg6 Al2 (OH)16 (CO3 ).4H2 O was the main hydrated phase identified in the AL-containing compositions. Due to this change in the hydration behavior of the refractories, the mixtures prepared with dead-burnt or magnesia fumes plus organic salt presented a longer setting time. Besides that, crack-free samples with improved permeability and green mechanical strength could be obtained when adding 0.5 wt% or 1.0 wt% of aluminum lactate to the tested castable compositions. Consequently, 1.0 wt% of the selected additive favored the design of refractories with enhanced properties and greater spalling resistance, as no explosion could be observed even when subjecting the prepared samples to severe heating conditions (20 °C/min).